It’s Tea Time: Interference of Ayahuasca Brew on Discriminative Learning in Zebrafish - Lobao-Soares, Bruno; Eduardo-da-Silva, Paulianny; Amarilha, Hugo; Pinheiro-da-Silva, Jaquelinne; Silva, Priscila F.; Luchiari, Ana Carolina (Frontiers in Behavioral Neuroscience, 2018)
Ayahuasca is a psychoactive brew traditionally used in shamanistic and vegetalistic rituals and has recently received lot of attention due to potential cognitive benefits. Ayahuasca effects are caused by the synergistic interaction of β-carbolines (harmine, harmaline and tetrahydroarmine) contained in Banisteriopsis caapi stalks combined with the dimethyltryptamine (DMT) from Psychotria viridis leaves, a potent agonist to serotonin receptors (5-HT). The present study approaches the effects of chronic and acute exposure to two Ayahuasca concentrations (0.1 and 0.5 ml/L) on the cognitive ability to discriminate objects in a one-trial learning task in zebrafish. Based on the combination of concentrations and exposure regimens, we divided adult zebrafish into five treatment groups: acute 0.1 and 0.5 ml/L, chronic 0.1 and 0.5 ml/L, and control 0.0 ml/L (n=20 for each group). Then we tested them in a memory task of object discrimination. Acute Ayahuasca exposed groups performed similarly to the control group, however chronically treated fish (13 days) presented both impaired discriminative performance and locomotor alterations. Overall, these results indicate that Ayahuasca is a potent psychoactive drug that, in chronic exposure, negatively affect mnemonic parameters in zebrafish. In single exposure it does not affect cognitive performance, but the higher concentration (0.5) affected locomotion. Moreover, we reinforce the importance of the zebrafish for behavioral pharmacological studies of drug screening, in special to psychedelic drug research.